Pathological Alterations in Dogs Resulting from Parasitism by Spirocerca Lupi - Elias, Fabiana; Barros, Rafaela Magalhães; Santos-Junior, Helvecio Leal; Eloi, Rômulo Santos Adjuto; Silva, Vinicius; Freitas, Fagner; Alves, Carlos Eduardo Fonseca (Acta Scientiae Veterinariae, 2016)
Background: Spirocercosis is considered to be an emerging pathological condition within veterinary medicine. The disease has worldwide distribution, although the greatest prevalence has been described in tropical and subtropical regions. The infection rate is affected by the interrelationships between the density of the dog population and intermediate hosts. The aim of this study was report the morphological and histopathological characteristics of natural infection by Spirocerca lupi in dogs from Distrito Federal, Brazil. Cases: Records were obtained from 10 dogs diagnosed with spirocercosis at the Pathology Sector, School of Veterinary Medicine, Uniao Pioneira de Integracao Social (UPIS), in Brasilia, Federal District. For six animals, the diagnosis was confirmed through necropsy. Two dogs presented aortic rupture, thus resulting in hemothorax and consequent hypovolemic shock. Another animal presented gastric nodules, erratic migration to the lungs and renal and splenic infarction due to aortic thromboembolism. One dog presented neoplastic transformation of the esophageal granuloma to osteosarcoma. The age of the dogs ranged from one to eight years and the weight ranged from 15 to 40 kg. The clinical histories were similar: regurgitation (10/10), emesis (5/10), dysphagia (7/10), weight loss (10/10), weakness (3/10) and dyspnea (4/10). Esophageal nodules measured 1 to 5 cm in diameter were observed in all the dogs and contained a large number of Spirocerca lupi specimens. Histologically, parasites were detected in adventitial and medial areas, surrounded by zones of necrosis and mixed inflammatory infiltrate. The stroma of the intimal tissue presented considerable fibrocellular proliferation (atherosclerosis), with areas of mineralization and ossification in the intimal and medial layers. An interesting finding of this study was atypical migration to the stomach and osteosarcoma case associated with parasitism by Spirocerca lupi. Discussion: Infection by Spirocerca lupi is very important in Brazil, however, there are few studies showing epidemiological, morphological and histopathological aspects of the parasite infection. In the Distrito Federal a large number of animals has died due to rupture of nodules located in the thoracic aorta, however, necropsy was not performed and these animals do not present confirmed diagnosis. Our results showed a major group of animals of large breed (6/10) follow by medium (3/10) and small (1/10) breeds. The incidence of spirocercosis is greater in medium to large-sized dogs because these animals remain outside of the domestic area for longer times than do small-sized animals. In this study, there was greater prevalence in mongrels. Nonetheless, breeds such as Cocker Spaniel, Borzoi, German Shepherd and Great Dane have also been affected by this condition. In general, the majority of free-living dogs are mongrels and the parasitosis rate is high among dogs of this type in enzootic areas. The great prevalence of adult dogs is related to the characteristics of the parasite’s life cycle, along with difficulty in making the diagnosis in animals under six months of age. We did not found young dogs showing infection by Spirocerca lupi. The age range between four and twelve years is most affected. Although the number of dogs diagnosed with spirocercosis has been increasing continuously in the Distrito Federal, it is commonly only identified through necroscopic examinations. Therefore, measures need to be taken towards making early diagnosis and appropriate treatment, in order to reduce the death rate. Due to the scarcity of data in the Brazilian literature about this condition, the present study and future studies and data-gathering are of prime importance. Keywords: aneurysms, dogs, necropsy, Spirocerca lupi.